PENYELESAIAN SENGKETA EKONOMI DAN BISNIS MELALUI ARBITRASE INTERNASIONAL (Studi Kasus Pertamina Vs Karaha Bodas) - Erni Dwita Silambi (EKONOMI & SOSIAL, 2012)
Interesting case that drew international attention to the internatinal society case between Pertamina Vs Karaha Bodas Company, where the obvious interest of a very different friction between the two, especially the company Karaha Bodas is a company incorporated under the capital flows both from within and from outside, where more priority to the company's goal is profit oriented and the other national companies or pertamina prefer the national interest.